PEMIKIRAN PENDIDIKAN ISLAM OMAR MUHAMMAD TOUMY DALAM PERSPEKTIF PROGRESIVISME - Muhamad Agus Mushodiq; Yusuf Hanafiah (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: This article explores the progressive style of Islamic education and education philosophy initiated by Omar Muhammad at-Toumy Asy-Syaibani. In conducting the exploration, the author uses a qualitative literature research method with the primary source of the book Falsafatu at-Tarbiyah al-Islamiyah by Omar at-Toumy. The results of this paper are a progressive style in the concept of Omar's Islamic education philosophy, including (1) the concept of Tawazun (balanced) and I'tidal (proportional) applied by Omar in formulating the philosophy of Islamic education accommodating the characteristics of progressivism in education in general and at the same time providing a new color in Islamic progressivism. Omar's concept of tawazun was poured into seeing reality, seeing the process of humans getting knowledge, and sources of knowledge and knowledge that are considered valid. (2) Emphasizing individual and societal change for the better, (3) The philosophy of Islamic education is following the community environment's realities (environmentalism) and can be practiced, not utopian ideas. (4) The philosophy of Islamic education is dynamic (dynamic) which can be changed at any time according to the demands of the times (5) Humans (education subjects) as creatures (natural realities) are the best according to Islamic teachings and have intelligence (instrumentalism) as natural resources and potential in solving all problems in the world, besides that he can prosper or take advantage of all the potential that exists in his life (6) The principle of justice and equality in society (students). A progressive style can be seen in (1) The existence of practical and realistic concepts in Islamic education, not only dwelling on information and theory, (2) According to him, an educator must maintain the differences that students have. , given that students have different potentials. (3) The goals of education are also very dynamic, they are adapted to the times, and (4) The curriculum in Islamic education must also be dynamic and flexible with the times. Keywords: Progressive,Tawazun; Tagyir; Omar Muhammad at-Toumy; Islamic Education Philosophy.